Development of Some Larval Nematodes in Experimental and Natural Animal Hosts: An Insight into Development of Pathological Lesions vis-a-vis Host-Parasite Interactions. (23rd December 2013) - Chowdhury, N.; Sood, N. K.; Lal, Shyam; Gupta, Kuldip; Singla, L. D.
Abstract : Infective third-stage larvae of three spiruroid nematodes, Ascarops strongylina and Physocephalus sexalatus of pigs and Spirocerca lupi of dogs, were recovered from 14 species of coprophagous beetles belonging to 4 different genera. These larvae were fed to rabbits and/or guinea pigs to study their development in these experimental hosts. Larvae of A. strongylina reached the adult stage in all rabbits and one guinea pig. The adult worms recovered in these hosts were 40% and 4%, respectively, and became diminutive in comparison to their natural hosts. The larvae of P. sexalatus became reencysted in the gastric wall of rabbits inducing marked pathological changes. The infective larvae of S. lupi became reencapsulated in the stomach wall of the rabbit and also showed development in the aortic wall. Adults of Toxocara canis of dog, collected from 5 different regions of the Indian subcontinent, varied significantly in size. The mouse passage of infective larvae of one of these types led to the recovery of the adults from the experimental dogs that were smaller in size and caused severe pathology in natural experimental hosts. Developmental effects shown in experimental hosts and host specificity are of value in understanding the evolution of nematode parasitism.